2009
DOI: 10.1017/s1751731108002978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age at weaning on the physiological stress response and temperament of two beef cattle breeds

Abstract: The study was conducted to evaluate the effect of age at weaning and breed on the stress response of calves to weaning and their temperament. At calving, 14 Parda de Montañ a calves and 14 Pirenaica calves were randomly assigned to either early weaning (at 90 days) or traditional weaning (at 150 days) treatment. During nursing, calves were allowed to suckle their dams twice a day for 30 min. After weaning, calves were placed in an adjacent barn without access to their dams, where they remained for 7 days. On d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
47
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 28 publications
12
47
2
Order By: Relevance
“…The course of the neutrophil : lymphocyte ratio did not show different changes during the study period between castration and weaning groups, too. Blanco et al (2009) weaned calves at 90 or 150 days of age and also did not find an effect of weaning on neutrophil or lymphocyte proportions until 1 week after weaning. A contrary observation was made by Hickey et al (2003), who found decreased lymphocyte and increased neutrophil proportions as well as increased neutrophil : lymphocyte ratios in weaned compared with control calves until 1 week after the treatment.…”
Section: Behaviourmentioning
confidence: 76%
“…The course of the neutrophil : lymphocyte ratio did not show different changes during the study period between castration and weaning groups, too. Blanco et al (2009) weaned calves at 90 or 150 days of age and also did not find an effect of weaning on neutrophil or lymphocyte proportions until 1 week after weaning. A contrary observation was made by Hickey et al (2003), who found decreased lymphocyte and increased neutrophil proportions as well as increased neutrophil : lymphocyte ratios in weaned compared with control calves until 1 week after the treatment.…”
Section: Behaviourmentioning
confidence: 76%
“…In the present study, a number of alterations to the blood leukogram were identified. Weaning and housing have both been previously shown to increase total leukocyte number (Blanco et al, 2009;Hickey et al, 2003b;Lynch et al, 2010) as a result of fluctuations in a number of leukocyte subpopulations, particularly neutrophils. Elevations in endogenous or exogenous glucocorticoids are reported to cause a dramatic shift in the haematological profile of peripheral blood cells resulting in leukocytosis which is marked by neutrophilia and lymphopenia (Burton et al, 2005).…”
Section: Variablementioning
confidence: 99%
“…Although some studies have shown that this response is activated through the measurement of fibrinogen, ceruloplasmin and SAA (Arthington et al, 2003(Arthington et al, , 2008Blanco et al, 2009;Carroll et al, 2009), others have reported that concentrations of fibrinogen and haptoglobin are not affected by weaning (Hickey et al, 2003b).…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Weaning elicits a stress response in both cows (Lefcourt and Elsasser, 1995;Haley, 2006;Lynch et al, 2010a) and calves (Blanco et al, 2009;Lynch et al, 2010b and, thus reducing their welfare. For example, cows begin pacing and vocalizing immediately after their calves are weaned, showing that it is a stressful event for them 2015).…”
Section: Introductionmentioning
confidence: 99%